A new species of direct-developing frog of the genus Eleutherodactylus (Anura: Eleutherodactylidae) from the Pacific lowlands of Guerrero, Mexico - Palacios-Aguilar, Ricardo; Santos-Bibiano, Rufino (Zootaxa, 2020)
We describe a new species of direct-developing frog of the genus Eleutherodactylus from the Pacific lowlands of Guerrero, Mexico. Eleutherodactylus erythrochomus sp. nov. is a saxicolous species that inhabit caves or crevices formed by groups of large granitic boulders, which create contrasting climatic characteristics to the surrounding habitat. This new species is geographically restricted to the Tierra Colorada region, a biologically important area that harbors microendemic taxa. This species is the first microendemic amphibian described from this region. The new species can be easily differentiated from congeners by having long and slender limbs, lacking a lumbo-inguinal gland, and expanded digital pads. Further exploration and conservation measures should be conducted at the type locality of this new species in order to preserve and understand the herpetofaunistic composition occurring therein.